Registros norteños de Mazama temama y de Leopardus wiedii en el noreste de México - Hernández Jasso, Roberto Emmanuel; Manuel De la Rosa, Zavdiel Alfonso; Mendoza Gutiérrez, Gabriela Rubí; Soria Díaz, Leroy (Revista Bio Ciencias, 2024)
For the northeast of Mexico and particularly in the state of Tamaulipas, the records of presence of Mazama temama and Leopardus wiedii are limited to the El Cielo biosphere reserve and it is not unknown how these species have expanded their distribution. Between September 2020 and November 2021, a mammal monitoring project was carried, using trap cameras in the southern portion of Altas Cumbres, Victoria municipality, Tamaulipas. A total of four simple georeferenced sampling stations were installed, separated by 300 m from each other in a straight line. Each station was established near the passage of fauna. Among the native faunas that were documented, the presence of two species that are recorded for the first time for the area stands out. The first is the red brocket deer (M. temama) and the second is the margay (L. wiedii), photographed for the first time on May 3, 2020 around 00:00 h, and on September 2, 2020 around 00:00 h, respectively. The presence of a pair of red brocket deer not only increases the species’ northern record to about 61.69 km, it also contributes to the knowledge of its biology. While, for margay, the northern limit of the state is extended with 61.80 km to the previous record in the El Cielo biosphere reserve; and among the most northeastern population located in Nuevo León with 47.09 km, being a key link between these populations.